Complaint to the Utility Regulator by Manufacturing Northern Ireland & Powerhouse Generation Limited (on behalf of Severfield (NI) Limited, Dunbia (Northern Ireland), LGen Power Limited & Ready Eggs Products Limited) in Relation to Northern Ireland Electricity Networks Limited's Treatment of Maximum Export Capacity : Determination.: Determination. (2017) - Northern Ireland., Utility Regulator,
No abstract available